1989
DOI: 10.1080/00319108908030616
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Ultrasonic Behaviour of Acetophenone and Alcohol Mixtures

Abstract: Excess volumes and sound velocities for binary liquid mixtures of acetophenone with n-alcohols and ialcohols are measured at 303.15 K. The sound velocity and density data are used to calculate the isentropic compressibilities (k,) and deviations in isentropic compressibilities (AkJ. The values of V' are negative in all the systems except in the system, acetophenone + n-heptanol wherein the V L values are positive.Deviations in isentropic compressibilities are negative in all the systems over the entire range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…can be studied by measurement of speeds of sound in liquid mixtures. Also isentropic compressibility data for the mixtures of acetophenone with 1-alkanols, benzene and substituted benzenes, and chloroethanes and chloroethenes were also reported earlier at 303.15 K. The experimental sound velocity data have been analyzed in terms of free length theory (FLT) and collision factor theory (CFT)…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…can be studied by measurement of speeds of sound in liquid mixtures. Also isentropic compressibility data for the mixtures of acetophenone with 1-alkanols, benzene and substituted benzenes, and chloroethanes and chloroethenes were also reported earlier at 303.15 K. The experimental sound velocity data have been analyzed in terms of free length theory (FLT) and collision factor theory (CFT)…”
Section: Introductionmentioning
confidence: 91%
“…Thermodynamic excess properties of binary liquid mixtures have been very useful in obtaining information on the intermolecular interactions and geometrical effects in the systems. , Furthermore, thermodynamic properties of binary mixtures, containing components capable of undergoing specific interactions, exhibit significant deviation from ideality arising not only from difference in molecular size and shape but also due to structural changes. A survey of the literature has shown that V E data for the binary mixtures of acetophenone with 1-alkanols, benzene and substituted benzenes, and chloroethanes and chloroethenes have been reported. It is well-known that the ultrasound technique has a wide range of applications such as in industry and in equipment testing.…”
Section: Introductionmentioning
confidence: 99%
“…This shows the contraction of volume which shows the presence of strong intermolecular forces between unlike molecules than the like molecules. The intermolecular interactions are formed between the oxygen atom of -OH group of alcohols and the carbonyl group of p-chloroacetophenone 9 . Excess molar volumes (V E ) depends on some important factors like 10 .…”
Section: Excess Molar Volumes (V E )mentioning
confidence: 99%
“…The excess property study has been used for the design of equipment in heat transfer, fluid mechanics, process calculation and process control. The investigations have been carried out on phenols [1][2][3] and alcohols [4,5] and more study on phenones [6][7][8][9][10][11][12] and on methyl acetate [13] has been reported. Literature survey shows that no work has been reported on these mixtures at such temperatures.…”
Section: Introductionmentioning
confidence: 99%